Influence of Cold Maceration Time on Chromatic and Microbiological Characteristics of Cabernet Sauvignon Wines - Kuchen, B.; Vazquez, F.; Mestre, M.V.; Toro, M.E.; Maturano, Y.P. (South African Journal of Enology and Viticulture, 2018)
The pre-fermentative cold soak (CS) is proposed so as to extract and stabilise polyphenolic compounds in wines. CS is applied empirically to Cabernet Sauvignon in Cuyo, Argentina; however, there is poor scientific background on this technique. The aim was analyse the effect of cold soak time on colour parameters such as total polyphenols, total anthocyanins, tannins, colour and polymerisation indexes. Moreover, Saccharomyces and non-Saccharomyces populations were studied to evaluate their impact on colour. Cabernet Sauvignon must (Pedernal, San Juan) was distributed into four vessels: CONTROL (CT): simultaneous maceration and alcoholic fermentation (AF) with commercial yeast D254; T1: CS for two days; T2: CS for five days; and T3: CS for seven days. T1, T2 and T3 were maintained at 4 ± 1°C during CS. They were later inoculated with D254 (AF: 22 ± 1°C). The total polyphenol index (TPI), total anthocyanins (TA) and tannins were quantified during CS and AF. The colour index (CI) and polymerisation index (PI) were determined at the end of AF. The total yeast populations of Saccharomyces and non-Saccharomyces were quantified during CS and AF. The highest values of TA, tannins, TPI and PI were obtained by CT. This treatment also registered the highest total yeast population and the highest total yeast death. The highest CI was observed in T3. When Saccharomyces was found at the end of CS (T1 and T2), it dominated the alcoholic fermentation in the early stages (not observed in CT and T3). The use of the pre-fermentative CS technique in Cabernet Sauvignon wines is promising for young wines due to the increased colour obtained.